Brazilian songs in a French university: classroom practices from the perspective of literomusical literacy - Alves, Adriana Celia [UNESP] (EDIPUCRS, 2019)
This study aims to discuss the planning of Portuguese as an additional language course that uses the song as a guiding instrument for the classes. The research involved intermediate level students of a University Diploma of Brazilian Portuguese, a short course offered in the research institution in order to offer a deeper study of Brazilian language and culture for academic and professional purposes. Based on semistructured questionnaires, students' profiles for learning the Portuguese language in the Brazilian variant, a profile was built to design the lessons. From the perspective of literomusical literacy (Coelho de Souza, 2014) we reflected on the use of musical genres in the Portuguese as an additional language classroom in order to explore the linguistic, cultural and socio-historical aspects of the song, in order to provide students an amplified view of language and Brazilian culture.
Canções brasileiras em uma universidade francesa: práticas de sala de aula a partir da perspectiva do letramento literomusical
Keywords: literomusical literacy; songs; teaching of PFL/PAL